Microfluidics: Stochastic and Age‐Dependent Proteostasis Decline Underlies Heterogeneity in Heat‐Shock Response Dynamics (Small 30/2021). Issue 30 (28th July 2021) - Vertti‐Quintero, Nadia; Berger, Simon; Casadevall i Solvas, Xavier; Statzer, Cyril; Annis, Jillian; Ruppen, Peter; Stavrakis, Stavros; Ewald, Collin Y.; Gunawan, Rudiyanto; deMello, Andrew J.
Abstract : In article number 2102145, Collin Y. Ewald, Rudiyanto Gunawan, and co‐workers highlight a microfluidic device used for sorting adult C. elegans populations—in a high‐throughput manner—based on individual GFP expression. The heterogeneous dynamic heat‐shock response, its relation to proteostasis, and how it can predict lifespan are thoroughly studied. Image credit: Mrs. Yujia Ma.